67. Agreement Among Bayesian Dosing Software for Calculating Vancomycin Area Under the Curve. (4th December 2021) - Pineda, Ross; Kanatani, Meganne; Davis, Matthew R; Sim, Myung-Shin; Deville, Jaime; Pham, Christine
Abstract: This abstract has been withdrawn.